Pre-deployment threat learning predicts increased risk for post-deployment insomnia: Evidence from the Marine Resiliency Study. (December 2022) - Hunt, Christopher; Stout, Daniel M.; Tie, Ziyun; Acheson, Dean; Colvonen, Peter J.; Nievergelt, Caroline M.; Yurgil, Kate A.; Baker, Dewleen G.; Risbrough, Victoria B.
Abstract: Insomnia is a common and impairing consequence of military deployment, but little is known about pre-deployment risk factors for post-deployment insomnia. Abnormal threat learning tendencies are commonly observed in individuals with insomnia and maladaptive responses to stress have been implicated in the development of insomnia, suggesting that threat learning could be an important risk factor for post-deployment insomnia. Here, we examined pre-deployment threat learning as a predictor of post-deployment insomnia and the potential mechanisms underlying this effect. Male servicemembers ( N  = 814) completed measures of insomnia, psychiatric symptoms, and a threat learning task before and after military deployment. Threat learning indices that differentiated participants with versus withoutinsomnia at post-deployment were tested as pre-deployment predictors of post-deployment insomnia. Post-deployment insomnia was linked to elevations on several threat learning indices at post-deployment, but only higher threat conditioning, as indexed by higher threat expectancy ratings to the danger cue, emerged as a pre-deployment predictor of post-deployment insomnia. This effect was independent of combat exposure levels and partially mediated by greater post-deployment nightmares. The tendency to acquire stronger expectations of aversive events following encounters with danger cues may increase risk for post-deployment insomnia, in part due to the development of more severe nightmares. Highlights: Examined pre-deployment threat learning as a predictor of post-deployment insomnia. Sample consisted of 814 active-duty servicemen. Higher pre-deployment fear conditioning predicted greater post-deployment insomnia. The effect was partially mediated by post-deployment nightmares. The effect was observed for subjective but not physiological measures of fear.